The Development of Integrated Science Instructional Materials to Improve Students’ Digital Literacy in Scientific Approach - Asrizal, A.; Amran, A.; Ananda, A.; Festiyed, F.; Sumarmin, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
Integrated science and integration of literacy skills are relevant issues to be investigated in science education. This research aimed at determining the validity of integrated science materials and examining the practicality and effectivity of the use of integrated science materials in the scientific approach. The type of this research was research and development. The development of integrated science materials consists of seven stages, namely identifying potentials and problems, collecting information, designing a product, validating the product, revising product, doing limited testing, and revising product. Instruments for collecting data included validity assessment, practicality assessment, written test, and performance assessment. The data were analyzed by descriptive statistics and paired comparison test. Based on the data analysis, there were three results of this research. First, the validity of integrated science instructional materials classified as very high with an average value of 83.2. Second, the integrated science instructional materials were practical according to the science teachers and students with an average value of 86.11 and 89.66 respectively. Third, the integrated science instructional materials were effective in the scientific approach to improving the aspects of knowledge and digital literacy including scientific, functional, and visual literacy at 95% confidence level. These results indicated that employing integrated science instructional materials could overcome the problem of integrated science teaching and improve the digital literacy of students in terms of scientific, functional, and visual literacy. These digital literacy components are also useful for students to get success in their real future life.